2019
DOI: 10.1093/imamat/hxz007
|View full text |Cite
|
Sign up to set email alerts
|

Effect of random forcing on fluid-lubricated bearing

Abstract: A model for a fluid lubricated bearing is derived for operation under conditions where external forces are subject to random fluctuations that may act to destabilise the bearing. The fluid flow through the bearing is described by a Reynolds equation for incompressible flow and is coupled to the axial displacement of the bearing faces as modelled by spring-mass-damper systems. Representative dynamics of a highly rotating bearing subject to external potentially destabilising random forcing is developed. An exter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…A similar trend is seen for coloured noise, with α = 100. Investigations show increasing the coloured noise parameter α, results in the average time at which the face clearance becomes as small as the prescribed tolerance E[τ δ ] tending to the values obtained for white noise [19]; results for white noise and coloured noise in Figure 5 are similar. These results can help aid bearing design by giving an indication of average bearing lifetime for types of external disturbances and force coupling parameters.…”
Section: Resultsmentioning
confidence: 67%
See 4 more Smart Citations
“…A similar trend is seen for coloured noise, with α = 100. Investigations show increasing the coloured noise parameter α, results in the average time at which the face clearance becomes as small as the prescribed tolerance E[τ δ ] tending to the values obtained for white noise [19]; results for white noise and coloured noise in Figure 5 are similar. These results can help aid bearing design by giving an indication of average bearing lifetime for types of external disturbances and force coupling parameters.…”
Section: Resultsmentioning
confidence: 67%
“…The associated solution notation for ( 14) is g(t) = g s,g0,z0 (t), z(t) = z s,g0,z0 (t), t ≥ s; g(s) = g 0 , z(s) = z 0 are the initial condition at t = s. If s = 0 the we write g g0,z0 (t), z g0,z0 (t) for compactness. Existence and uniqueness of the solution to (14), as well as boundedness of its moments was shown in [19]; this analysis formally demonstrated that g g0,z0 (t) can never become zero, thus that a positive face clearance is always maintained, although it may become arbitrary small. The time at which the face clearance g(t) first reaches a small given tolerance, δ > 0, is of interest.…”
Section: Numerical Techniquementioning
confidence: 83%
See 3 more Smart Citations